ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI PADI SAWAH DI DESA LAANTULA JAYA KECAMATAN WITAPONDA KABUPATEN MOROWALI - Widya Ningrum, Effendy, Ninis (AGROTEKBIS, 2016)
This study aims to determine the income feasibility of paddy rice farming in village of Laantula Jaya, subdistrict of Wita Ponda, Morowali district. Determination of Respondents done using simple random method (Simple Random Sampling). The number of samples taken as many as 31 people from the population of 110 people. The analytical tool used was income analysis and feasibility analysis. Anailisis results showed that the average revenue of the paddy rice farmers in the village in Laantula Jaya subdistrict Wita Ponda Morowali district of Rp.11.922.586,20/1.19 ha/Planting Season or Rp. 10.018.980 million/ha/Planting Season, the average total cost of Rp. 7.029.852,00/ 1.19 ha/Planting Season or Rp. 5.907.439,00/ha/Planting Season, while the average total revenue of Rp. 4.892.729,00 /1.19 ha/Planting Season or Rp. 4.111.537,00/ha/Planting Season. The results of the analysis of R / C showed that paddy rice farming in the village of Laantula Jaya, subdistrict Wita Ponda, Morowali district deserves can be pursued. This is evidenced by the value of R / C obtained by 1.69. This means that any expenditure of Rp. 1 will generate revenue by 1.69.